Prices of high-tech products, mismeasurement, and pace of innovation - Stephen D. Oliner; Daniel E. Sichel; David M. Byrne (American Enterprise Institute (AEI), 2017)
The authors argue that the pattern of multifactor productivity (MFP) growth across industries may presage a second wave of productivity advance supported by the digital economy.
Keywords: A; 330; Innovation; technology; productivity; productivity growth